Pengaruh Konflik Peran, Ketidakjelasan Peran, Independensi, dan Komitmen Organisasi Terhadap Kinerja Auditor (Studi empiris pada Kantor Akuntan Publik di Surakarta dan Semarang) - Ismarhadi, Iqbal; , Dra Rina Trisnawati, Ak, M,Si, PhD (2016)
The purpose of this study is to analyze and to provide empirical evidene about role conflict, role ambiguity, independence, and organizational commitment to auditor performance. The population in this research are auditors who work in the public accountant office in Solo and Semarang. The sampling method used is convenience. The research data was obtained from questionnaires. The data analysis method used is multiple linear regression analysis, where role conflict, role ambiguity, independence, and commitment of organizations as independent variable while auditor performance as dependent variable. The results of this study indicate that the role conflict, role ambiguity, independence, and organizational commitment have significant effect on auditor performance. This research also proves that role conflict, role ambiguity, independence, and organizational commitment influence on audit of quality, when role ambiguity not affect on auditor performance.